2020
DOI: 10.3390/ma13245757
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microstructure and Chemical Composition on Microhardness and Wear Properties of Laser Borided Monel 400

Abstract: In this study, wear properties of Monel 400 after laser alloying with boron are described. Surfaces were prepared by covering them with boron paste layers of two different thicknesses (100 µm and 200 μm) and re-melting using diode laser. Laser beam power density was equal to 178.3 kW/cm2. Two laser beam scanning velocities were chosen for the process: 5 m/min and 50 m/min. Surfaces alloyed with boron were investigated in terms of wear resistance, and the surface of untreated Monel 400 was examined for comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Consequently, surface laser alloying is widely used not only for different stainless steels, such as 1.4550 [12], 17-4PH [14], and 316L [16,17], but also for a variety of other steels, for example, 41Cr4 steel [18], C45 steel [19], 145Cr6 tool steel [20], Vanadis-6 tool steel [21,22], and so on. The use of amorphous boron is important in laser surface alloying, and this has been confirmed in the above-cited works and some others [23,24].…”
Section: Introductionmentioning
confidence: 59%
“…Consequently, surface laser alloying is widely used not only for different stainless steels, such as 1.4550 [12], 17-4PH [14], and 316L [16,17], but also for a variety of other steels, for example, 41Cr4 steel [18], C45 steel [19], 145Cr6 tool steel [20], Vanadis-6 tool steel [21,22], and so on. The use of amorphous boron is important in laser surface alloying, and this has been confirmed in the above-cited works and some others [23,24].…”
Section: Introductionmentioning
confidence: 59%
“…After diffusion, the specimens were cleaned from powder residues and degreased using acetone. The advantage of using the diffusion boriding process in comparison to the application of precoat in the form of paste [23][24][25] is the maintenance of a constant thickness on the entire surface of the specimen. In addition, the thickness of the diffusion layer can be controlled by extending or reducing the diffusion time.…”
Section: Methodsmentioning
confidence: 99%
“…In the publications that are available, the authors managed to find a single publication discussing diffusion boriding of Ni-Cu alloys [21]. Publications typically focus on the use of boron as a component of the additive material (powder) used in the laser cladding process (laser alloying [22][23][24][25], laser cladding [26,27]). In [27], a NiCrSiB coating was produced on Monel 400 using a laser cladding method, which was to improve resistance to cavitation erosion and corrosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kukliski studied laser-treated samples of Monel 400 coated with boron. He found that alloying hardens the surfaces [ 41 ]. Mehrpouya showed that the microstructure of the H13 tool steel changed after laser treatment in the reworked layer, HAZ, and base metal.…”
Section: Literaturementioning
confidence: 99%